Harvest time optimization leads to the production of native cassava starches with different properties - de SouzaYes Fernandes, Daiana [UNESP]; dos Santos, Thaís Paes Rodrigues [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Leonel, Magali [UNESP] (Elsevier, 2019)
The starch market is very diverse and demanding regarding the functional characteristics of the product. However, no technique based on the management of cassava root harvest time has been applied to obtain starches with different properties. Thus, in this study, cassava roots were harvested at different times and the structure and physicochemical properties of their starches were analyzed. Results indicated the time points in the first growth cycle of plants when all parameters associated with root growth were at their highest values. It was also observed that changes in the time of harvest leads to the production of starches with different granule size, crystallinity, and content of amylose and phosphorus, which resulted in changes in the thermal and pasting properties, as well as in the solubility of the starches and swelling power; that is, on the main determinant characteristics for applicability of the starches. Planned agricultural production monitoring, coupled with the analysis of the main starches characteristics for large-scale cassava crops, can provide commercial benefits for both farmers and industry, as it is possible to obtain starches with desired physicochemical characteristics for varied applications.
Keywords: Cassava; Growth phases; Starch properties